The urban–rural divide1: Perceptions of income and social inequality in Central and Eastern Europe. Issue 2 (4th January 2016) - Binelli, Chiara; Loveless, Matthew
Abstract: A vast literature has related perceptions of income inequality to individuals' income: the higher the level of income, the less inequality is perceived. Here, examining the perceptions of income and social inequality, we argue that rural or urban residence affects both inequality perceptions and the impact of income on these perceptions. We test the theory using survey data from 12 Central and Eastern European countries and we find that income negatively affects inequality perceptions but only in urban areas. These findings confirm the importance of accounting for urbanity to understand what drives individuals' perceptions of inequality.